First-Principle Study of the Structural, Electronic and Magnetic Properties of Bulks Cu2O and CuO - Acharya, Dipak Kumar; Gurung, Anil Kumar; Yadav, Tarani Prasad; Paudel, Gyan Prasad (Journal of Physical and Life Sciences, 2024)
First-principle calculation was applied to explore structural, electronic and magnetic properties of both the bulks Cu2O and CuO. Density Functional Theory (DFT) based calculators of exchange-correlation functions LSDA+U, SGGA+U and SMGGA were used for the comparatively study of both oxides. These calculations showed the diamagnetic and the antiferromagnetic behaviors of both the p-type semiconductors Cu2O and CuO respectively. The calculators measured the band gaps of Cu2O approximately 0.70, 0.56 and 0.79 eV while the band gaps of CuO approximately 2.42, 2.22, and 2.20 eV respectively. The corresponding experimental values are 2-2.2 eV and 1.2-1.9 eV. These calculators are more accurate for the measurement of the band gap of CuO than the band gap of Cu2O. Both oxides are used in various applications as photo catalysis, magnetic storage media, sensors, electronics etc.